2017
DOI: 10.1177/1687814017697895
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation on the shock-wave and flow structures in a transonic contra-rotating axial compressor

Abstract: Numerical simulation has been conducted on a transonic contra-rotating axial compressor to investigate the shock wave and flow characteristics under various operation conditions. Results indicate that the shock-wave structure in the downstream rotor (Rotor 2) of transonic contra-rotating axial compressor is more complex than that in the upstream rotor (Rotor 1). Under the choke condition, a double shock-wave structure appears in the Rotor 2 leading to serious loss. Moving to the design condition, a single shoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…As shown on the left side of Figure 10, the high EGR zone, which also represents losses due to the separation bubble, vanishes as the compressor operates at lower mass flow rates. 48
Figure 10.Separation-induced transition and high EGR region.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown on the left side of Figure 10, the high EGR zone, which also represents losses due to the separation bubble, vanishes as the compressor operates at lower mass flow rates. 48
Figure 10.Separation-induced transition and high EGR region.
…”
Section: Resultsmentioning
confidence: 99%
“…As shown on the left side of Figure 10, the high EGR zone, which also represents losses due to the separation bubble, vanishes as the compressor operates at lower mass flow rates. 48 For in-depth study of the leading-edge boundary layer, the line integral values of the EGR and the spanwise averaged values of streamwise velocity us, flow angle, β 0 , static pressure p, and de-Haller number 12 were measured at was measured using the same directions for the blade angle β 1s (see Figure 2). β 0 is used to approximate the size of the dead-air zone.…”
Section: Inlet Egrmentioning
confidence: 99%
“…However, the mechanisms of the TCV unsteadiness are not clear yet. Many researchers [4][5][6][7][8][9][10][11] noticed that there was a strong oscillation related to TCV in the rotor tip for some compressors, especially under the near-stall (NS) conditions. By the means of Fourier transformation (FT), it was found that the frequency of the oscillation was approximately half of the blade passage frequency (BPF).…”
Section: Introductionmentioning
confidence: 99%